LAPORAN ARUS KAS UNTUK MENILAI KINERJA KEUANGAN PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BEI - Raden Irna Afriani; Novi Handayani; Eti Kuryati (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study is to analyze cash flow statements to assess the financial performance of companies engaged in agriculture listed on the Indonesia Stock Exchange in 2017-2021. The research method used is descriptive qualitative research. The data used is secondary data, namely the complete financial statements of agricultural sector companies, totaling 6 companies listed on the Indonesia Stock Exchange (IDX) using purposive sampling. The analytical technique used is using the cash flow ratio by comparing each cash flow statement from each company engaged in the agricultural sector each year. The results show that the agricultural companies studied in general have good performance, if examined from the ratio of cash flows to interest, capital expenditures, and the ratio of cash flows to net income, but from the ratio of cash flows to current liabilities and total debt, the company the agricultural sector is underperforming